Answer :
Answer:
(x - 7)² + (y - 5)² = 116
Step-by-step explanation:
equation of a circle:
(x - h)² + (y - k)² = r²
where (h,k) is the centre and r is the radius
centre is the midpoint of the diameter:
(h,k) = (11+3)/2 , (-5+15)/2
(h,k) = (7,5)
diameter = sqrt[(15--5)² + (3-11)²]
diameter = sqrt(464) = 4sqrt(29)
radius = ½ diameter
radius = 2sqrt(29)
r² = 116
equation:
(x - 7)² + (y - 5)² = 116
Answer:
[x-7]^2 + [y-5]^2= 116
Step-by-step explanation:
General equation of a circle is
[x2 - xo]^2 + [y2- yo]^2 = r^2
Where xo and yo are coordinates of the circle at the origin.
But xo = [x2 + x1]/2
= 11 + 3 / 2 = 7
yo = [y2 + y1] / 2 = [-5 + 15] /2 = 5
x2= 11, x2= 3; y1= -5, y2= 15
[11-7]^2 + [15-5]^2 =
16+ 100=116 = r^2
From the expression below;
[x2-xo]^2 + [y2-yo] ^2 = r^2
[x1-xo]^2 + [y1-yo] ^2 = r^2
[x-7]^2 + [y-5]^2= 116